The taphonomy of a micromammalian faunal assemblage from the Saldanha Bay Yacht Club : a contribution to the study of the South African west coast palaeoenvironments - Manthi, Fredrick Kyalo (Department of Archaeology, 2014)
Bibliography: leaves 129-146.